Increase of the mitotic activity of colonic mucosa in patients with multiple non-familial adenomatous polyps - Bandettini, L; Filipponi, F (The Italian journal of surgical sciences, 1985)
A histological study of colonic mucosa, including the measurement of the mitotic index, was performed in routinely processed specimens from control subjects and patients with multiple non-familial adenomatous polyps, to ascertain whether the onset of adenomatous polyps was accompanied by an increase in mucosal mitotic activity as compared with controls. The mitotic index of both the polyps and the mucosa 20 cm from the anal orifice of the same patients was significantly (P less than 0.01) higher than that of control 20 cm from the anal orifice and a shift of the mitotic activity from the lower two-thirds to the upper third of glands was observed in the polyps. These data suggest that an increase of mitotic activity in the superficial third of the glands as compared with controls plays a pathogenetic role in the onset of adenomatous polyps and that this phenomenon is accompanied by a diffuse increase of mitotic activity in the deeper two-thirds of the glands.